DIDACTIC PRINCIPLES OF READING SKILLS FOR FUTURE TEACHERS IN ENGLISH LANGUAGE TEACHING METHODOLOGY - Urinova Durdona Farkhodovna (Innovate Conferences, 2025)
In this era of globalization, there is a significant focus on fostering creativity across various domains. Creativity plays a crucial role in enhancing productivity and effectiveness in the workplace. The process of boosting creativity begins with nurturing creative skills. This article discusses the enhancement of creative abilities and offers useful advice for aspiring English educators. Additionally, the article is structured into an introduction, a main section, and a conclusion. The main section specifically addresses various strategies that future English teachers can utilize to cultivate their creative skills.
Keywords: Teaching English, language skills, reading skill, methods, didactics, didactic principles, methodology, creative methods, modern teachers, students, interactive activities.